Kinectics of the pulmonary phase of Schistosoma mansoni in mice treated with dexamethasone Cinética da fase pulmonar do Schistosoma mansoni em camundongos tratados com dexametasona - Marco Victor Hermeto; Rosilene Siray Bicalho; Alan Lane de Melo; Leógenes Horácio Pereira (Revista do Instituto de Medicina Tropical de São Paulo, 1990)
In the experimental schistosomiasis mansoni glucocorticoids cause a reduction in the worm burden when administered in the week of infection or, the longest, at the next week. In order to determinate the probable(s) site(s) of reduction of the worm burden, mice were infected with cercariae of LE strain of S. mansoni and dexamethasone was administered daily (50 mg/kg, subcutaneously) starting 1 hour before infection until the eighth day. Mice were sacrificed daily starting on the third day after infection until the ninth day, and schistosomula from lungs were collected. Six weeks after infection, the remaining mice were sacrificed and perfused for adult worm recovery. Analysis of the results showed that the non-treated mice presented larger numbers of lung larvae than the treated ones, and this difference was also found later in the worm burden in the portal system. This difference may reflect the early death of larvae in treated animals, before or after reaching the lungs. Na esquistossomose mansoni experimental, os glicocorticóides causam uma redução na carga de vermes quando administrados na semana da infecção, ou, no mais tardar, na semana seguinte. A fim de determinar o(s) provável(is) sí-tio(s) de redução da carga de vermes, camundongos foram infectados com cercárias da cepa LE de S. mansoni e dexametasona foi administrada diariamente (50 mg/kg, subcutaneamente), iniciando 1 hora antes da infecção e prosseguindo até o 8º dia. Os camundongos foram sacrificados diariamente, do 3º ao 9º dia pós-infecção, e os esquistossômulos foram coletados. Os camundongos remanescentes foram sacrificados seis semanas após a infecção e perfundidos para recuperação dos vermes adultos. A análise dos resultados mostrou que os camundongos não tratados apresentavam números maiores de larvas pulmonares que os tratados, sendo que esta diferença foi também encontrada mais tarde na carga de vermes do sistema porta. Esta diferença pode representar a morte precoce das larvas nos animais tratados, no período pele-pulmão de seu ...